Instruments of Innovation Security - Mikhaylova, Anna A.; Mikhaylov, Andrey S. (International Journal of Economics and Financial Issues, 2015)
This paper sets out a scientific debate on the phenomenon of innovation security and regional innovation security in particular. Authors suggest that innovation security should be considered as an independent type of regional security, along with economic, environmental, political, etc. security types. It is assumed that innovation security is one of the key imperatives of regional development along with the sustainability, competitiveness, and innovativeness. Article rests upon the analysis of the mechanisms and tools within the innovation policies of the highly innovative countries of the Baltic region – Denmark, Finland, Germany, Norway, and Sweden, which demonstrate an ‘unintended' application experience of the regional innovation security provision. The study underlines the most influential factors affecting the institutional framework of an innovation security establishment process. Paper concludes with a set of policy recommendations on regional innovation security in the context of contemporary socio-economic trends. Keywords: innovation security, innovation policy, innovation potential, region, Baltic region, BSR, Germany, Nordic countries, Russia, international cooperation JEL Classifications: D83; D85; F52; O33